Impact of small scale irrigation technology on women empowerment in Amhara national regional state of Ethiopia - Belainew Belete; Surafel Melak (Cogent Economics & Finance, 2020)
Even though there is a growing interest to empower rural women in all economic activities. Works of literature are scant to evaluate the role of small-scale irrigation technology on women empowerment. This study evaluates the impact of the adoption of small-scale irrigation technologies on women empowerment, where empowerment is measured by Women Empowerment in the Agricultural index. The propensity Score Matching (PSM) method was employed to identify comparable technology adopting and non-adopting sample households. Results of the average treatment effect on treated suggest adoption of small-scale irrigation technologies exacerbate the disempowerment of women. Hence, we suggest Policy and development interventions should give due emphasis on improving women's capacity to own and control resources and should be decision-makers.
Keywords: D02; J16; Q15; Q16; 330; impact; propensity score matching; small-scale irrigation technology; women empowerment in agricultural index